Inherited erythromelalgia due to mutations in SCN9A: natural history, clinical phenotype and somatosensory profile - McDonnell, Aoibhinn; Vollert, Jan (Brain, 2016)
Inherited erythromelalgia, the first human pain syndrome linked to voltage-gated sodium channels, is widely regarded as a genetic model of human pain. Because inherited erythromelalgia was linked to gain-of-function changes of sodium channel Na v 1.7 only a decade ago, the literature has mainly consisted of reports of genetic and/or clinical characterization of individual patients. This paper describes the pattern of pain, natural history, somatosensory profile, psychosocial status and olfactory testing of 13 subjects with primary inherited erythromelalgia with mutations of SCN9A , the gene encoding Na v 1.7. Subjects were clinically profiled using questionnaires, quantitative sensory testing and olfaction testing during the in-clinic phase of the study. In addition, a detailed pain phenotype for each subject was obtained over a 3-month period at home using diaries, enabling subjects to self-report pain attacks, potential triggers, duration and severity of pain. All subjects reported pain and heat in the extremities (usually feet and/or hands), with pain attacks triggered by heat or exercise and relieved mainly by non-pharmacological manoeuvres such as cooling. A large proportion of pain attacks (355/1099; 32%) did not involve a specific trigger. There was considerable variability in the number, duration and severity of pain attacks between subjects, even those carrying the same mutation within a family, and within individuals over the 12-13 week observation period. Most subjects (11/13) had pain between attacks. For these subjects, mean pain severity between pain attacks was usually lower than that during an attack. Olfaction testing using the Sniffin’T test did not demonstrate hyperosmia. One subject had evidence of orthostatic hypotension. Overall, there was a statistically significant correlation between total Hospital Anxiety and Depression Scale scores ( P = 0.005) and pain between attacks and for Hospital Anxiety and Depression Scale Depression scores and pain between attacks ( P = 0.001). Hospital Anxiety and Depression Scale scores for five subjects were below the threshold for mild anxiety or depression and none of the 13 subjects were severely anxious and/or depressed. Quantitative sensory testing revealed significantly increased detection thresholds for cold and warm stimuli at affected, compared to unaffected sites. By contrast, significantly decreased cold and heat pain thresholds were found at unaffected sites. Sensory profiles varied considerably between affected and unaffected sites, suggesting the existence of small fibre neuropathy in symptomatic sites. This in-depth clinical characterization of a well-defined inherited erythromelalgia population indicates the importance of characterizing the pain phenotype in individuals before undertaking clinical trials, given the inherent variability of pain both between and within inherited erythromelalgia subjects, even those within a family who carry the same mutation.
Gesehen am 17.04.2019